CONTRIBUTION OF STAVROPOL COOPERATORS TO HOUSING CONSTRUCTION IN THE REGION IN 1950s - A. K. Pechalov; L. V. Pechalova (Гуманитарные и юридические исследования)
The article is devoted to the problem which is not poorly highlighted in the scientific literature. The activity of producer's cooperatives in the sphere of housing construction in the Stavropol region as well as providing the population with dwellings is analyzed. The study refers to various sources and materials.